Physicochemical properties, sensory traits and storage stability of reduced-fat frankfurters formulated by replacing beef tallow with defatted bovine heart. (May 2019) - Rahman, M. Shafiur; Seo, Jin-Kyu; Zahid, Md. Ashrafuzzaman; Park, Jun-Young; Choi, Sung-Gil; Yang, Han-Sul
Abstract: The consumer interests for low-fat meat products are increasing to reduce obesity and chronic diseases. Reduced-fat frankfurter (RFF) was prepared by replacing beef tallow with defatted bovine heart (DBH) produced by supercritical–CO2 (SC-CO2 ) and hexane. Six different frankfurters i.e. control (20% beef fat), T1 (30% fat replacement with non-defatted bovine heart), T2 and T3 (20% and 30%, respectively, fat replacement with SC-CO2 –treated DBH), T4 and T5 (20% and 30%, respectively, fat replacement with hexane–treated DBH), were formulated. Physicochemical properties, sensory traits and storage stability of the control and RFFs were investigated. T3 had highest native proteins (18.50 g/100 g) resulting in increased viscosity, emulsion stability, hardness and redness ( a ⁎ ) with lowest energy value and cooking loss. T2 showed better sensory attributes than the control and other RFFs. Incorporation of SC-CO2 –treated DBH in frankfurter by replacing fat led to higher oxidative stability and lower microbial content during storage than the control, T1, T4 and T5. Highlights: Bovine heart was defatted using supercritical-CO2 (DBH–SC) and hexane. Reduced-fat frankfurters were prepared using defatted bovine heart by replacing beef tallow. DBH–SC incorporated sample had lower energy value and reduced coking loss. 20% fat replacement with DBH–SC led to better sensory attributes. DBH–SC incorporated samples had lower microbial content and higher oxidative stability.